INNOVATIVE TECHNOLOGY TO ENSURE SOCIAL HEALTH - Garashkina, N.V.; Druzhinina, A.A. (Tambov University Review. Series: Humanities, 2016)
The social health has strategic value for the development of society, social sphere, personality, as a result, an urgent task of the theory and practice of social work is the search for innovative technologies that ensure the social welfare of the population. The analysis of researches in the field of technological approach allowed to give the author's definition of technologies of social work as a system of knowledge, social practice and disciplines, aimed at effectively solving social problems. Technologies of saving and development of social health are defined as socio-pedagogical and innovative, so as technologies of positive socialization. Socialization is interpreted as the development of the personality and self-development of the personality in the process of mastering and reproduction of social culture at all age levels. For a conceptual foundation of innovative technologies it is important to understand the category of “social health” as a result of socio-pedagogical work. The integrated criterion of social health of the personality is her / his subjectivity in the process of socialization. The trend of the interaction of the social health environment and the personality allows it to be considered as basic approaches in the development of innovative technologies of socio-pedagogical support of the social health of the population environmental and learner-centered approaches. Groups and structure of technologies providing social health environment and personality are selected. The author's position about the prospects for research of innovative technologies, ensure the preservation of the social health of the individual and the environment is reflected and prospective areas of social work that will enhance the quality and effectiveness of activities, taking into account specific social needs and problems of citizens in the current situation and in the future are identified.